2021
DOI: 10.1111/dme.14685
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c combined with glycated albumin or 1,5‐anhydroglucitol improves the efficiency of diabetes screening in a Chinese population

Abstract: Aims: This study aimed to evaluate the ability of HbA 1c combined with glycated albumin (GA) or 1,5-anhydroglucitol (1,5-AG) to detect diabetes in residents of Jiangsu, China. Methods:The oral glucose tolerance test (OGTT) was performed on 2184 people in Jiangsu. HbA 1c , GA, 1,5-AG and other serum biochemical parameters were measured. Receiver operating characteristic curves were plotted to determine the optimal thresholds of HbA 1c , GA and 1,5-AG according to the Youden index. Results:(1) The optimal thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As can be seen in Table 2, the sensitivity for diagnosing diabetes increased slightly as the level of 1,5-AG increased, accompanied by sharp decreasing speci city. Notably, our previous study [20] showed that 23 µg/mL was a reasonable point for 1,5-AG to screen for diabetes. In this study, the sensitivity and speci city were 81.5% and 67.7%, respectively, at the point of 23.55 µg/mL.…”
Section: Baseline Characteristicsmentioning
confidence: 96%
“…As can be seen in Table 2, the sensitivity for diagnosing diabetes increased slightly as the level of 1,5-AG increased, accompanied by sharp decreasing speci city. Notably, our previous study [20] showed that 23 µg/mL was a reasonable point for 1,5-AG to screen for diabetes. In this study, the sensitivity and speci city were 81.5% and 67.7%, respectively, at the point of 23.55 µg/mL.…”
Section: Baseline Characteristicsmentioning
confidence: 96%
“…J Qian et al. ( 42 ) conducted a study of 2,184 people in Jiangsu Province which showed that the optimal threshold for 1,5-AG screening for diabetes was ≤23.0 μg/mL, and the sensitivity of HbA1c combined with 1,5-AG was 85% higher than HbA1c (70%). H Su et al.…”
Section: Progress Of Clinical Research On 15-ag For Diabetesmentioning
confidence: 99%
“…Combining 1,5-AG with HbA1c, FPG, and GA to screen for diabetes with high sensitivity and specificity is more conducive to clinical application. J Qian et al (42) conducted a study of 2,184 people in Jiangsu Province which showed that the optimal threshold for 1,5-AG screening for diabetes was ≤23.0 mg/mL, and the sensitivity of HbA1c combined with 1,5-AG was 85% higher than HbA1c (70%). H Su et al (43) discovered that the sensitivity of 1,5-AG combined with FPG screening for diabetes was 84.92% and the specificity was 91.45% higher than the GA combined with FPG (77.71% and 90.88%) or using the above-mentioned indicators alone.…”
Section: Normal Reference Range Of 15-ag and Its Influencing Factorsmentioning
confidence: 99%
“…The normal concentration of 1,5-AG is approximately 12–40 μg/mL. However, serum 1,5-AG concentrations have been found to decrease in patients with DM [ 6 , 7 , 8 ]. Several methods have been explored to detect the level of serum 1,5-AG in a sensitive and accurate way.…”
Section: Introductionmentioning
confidence: 99%